Oleic Acid Protects Against Insulin Resistance by Regulating the Genes Related to the PI3K Signaling Pathway - López-Gómez, Carlos; Santiago-Fernández, Concepción; García-Serrano, Sara; García-Escobar, Eva; Gutiérrez-Repiso, Carolina; Rodríguez-Díaz, Cristina; Ho-Plágaro, Ailec; Martín-Reyes, Flores; Garrido-Sánchez, Lourdes; Valdés, Sergio; Rodríguez-Cañete, Alberto; Rodríguez-Pacheco, Francisca; et al. (Journal of clinical medicine, 2020)
Background: The effects of different types of fatty acids on the gene expression of key players in the IRS1/PI3K signaling pathway have been poorly studied. Material and Methods: We analyzed IRS1, p85α, and p110β mRNA expression and the fatty acid composition of phospholipids in visceral adipose tissue from patients with morbid obesity and from non-obese patients. Moreover, we analyzed the expression of those genes in visceral adipocytes incubated with oleic, linoleic, palmitic and dosahexaenoic acids. Results: We found a reduced IRS1 expression in patients with morbid obesity, independent of insulin resistance, and a reduced p110β expression in those with lower insulin resistance. A positive correlation was found between p85α and stearic acid, and between IRS1 and p110β with palmitic and dosahexaenoic acid. In contrast, a negative correlation was found between p85α and oleic acid, and between IRS1 and p110β with linoleic, arachidonic and adrenic acid. Incubation with palmitic acid decreased IRS1 expression. p85α was down-regulated after incubation with oleic and dosahexaenoic acid and up-regulated with palmitic acid. p110β expression was increased and decreased after incubation with oleic and palmitic acid, respectively. The ratio p85α/p110β was decreased by oleic and dosahexaenoic acid and increased by palmitic acid. Conclusions: Our in vitro results suggest a detrimental role of palmitic acid on the expression of gene related to insulin signaling pathway, with oleic acid being the one with the higher and more beneficial effects. DHA had a slight beneficial effect. Fatty acid-induced regulation of genes related to the IRS1/PI3K pathway may be a novel mechanism by which fatty acids regulate insulin sensitivity in visceral adipocytes.